2014
DOI: 10.1038/ejhg.2014.77
|View full text |Cite
|
Sign up to set email alerts
|

Machado–Joseph disease in a Nigerian family: mutational origin and review of the literature

Abstract: Machado-Joseph disease (MJD) has been described in Africans, but no cases have been reported from Nigeria. Current MJD global distribution results from both the ancestral populations-of-origin and the founder effects of mutations, some as a consequence of the Portuguese sea travels in the 15th to 16th century. Two main ancestral haplotypes have been identified: the Machado lineage, which is more recent, predominant in families of Portuguese extraction, and the Joseph lineage, which is much older and worldwide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…[ 2 ] The only autosomal dominant SCA described in Nigeria was SCA3, also known as Machado–Joseph disease, which was detected in a family in Calabar, Cross River State. [ 3 ] We herein describe nine members of a family in Northwest Nigeria affected by SCA7, which was confirmed in three individuals through DNA analysis. We then review relevant literature on the subject.…”
Section: Introductionmentioning
confidence: 76%
“…[ 2 ] The only autosomal dominant SCA described in Nigeria was SCA3, also known as Machado–Joseph disease, which was detected in a family in Calabar, Cross River State. [ 3 ] We herein describe nine members of a family in Northwest Nigeria affected by SCA7, which was confirmed in three individuals through DNA analysis. We then review relevant literature on the subject.…”
Section: Introductionmentioning
confidence: 76%
“…The haplotypes described here covered at least the classical three SNPs, as proposed by the first paper that described SCA3/MJD ancestral haplotypes: A 669 TG/G 669 TG (rs1048755), C 987 GG/G 987 GG (rs12895357), and TAA 1118 /TAC 1118 (rs7158733) 37 . From these 13 publications, five included both SCA3/MJD index cases as well as controls, 11,37‐40 six included SCA3/MJD subjects only, 41‐46 and two studied the general population only 47,48 . Besides those three classical SNPs (rs1048755, rs12895357, and rs7158733), these studies included different combinations of 31 additional intragenic markers (other SNPs and the CAG repeat tract) and/or four short tandem repeats (STRs) close to ATXN3 .…”
Section: Resultsmentioning
confidence: 99%
“…We selected a set of 26 SNPs within a region of 4 kb encompassing the (CAG) n , based on (1) minor allele frequencies (MAF > 5%; Ensembl 1 ); (2) recombination hotspots (within the same haplotype block; The International Genome Sample Resource and The 1000 Genomes Project); and (3) sequence alignments of previously analyzed patients (to include SNPs that discriminate MJD lineages (Martins et al, 2012; Ogun et al, 2015); Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Geographical differences in disease prevalence may be explained by haplotype studies, as shown for Huntington disease (HD), with the highest risk HD haplogroups being found in Europe, while absent in East Asia (Warby et al, 2011). In MJD two de novo expansions seem to have occurred, and, so far, its presence in remote and ethnically diverse populations has been explained by genetic drift and founder effects (Gaspar et al, 2001; Martins et al, 2007, 2012; Ogun et al, 2015); This optimized protocol could clarify remaining questions about the origins and history of MJD mutations. By following the same pipeline to study other expanding loci , one could understand better disease prevalence and provide a clearer scenario about the occurrence of de novo expansions (Venkatesh et al, 2018).…”
Section: Protocol Design and Applicationsmentioning
confidence: 99%